Analisis Penerapan Klasifikasi Biaya sebagai Dasar PengambilanKeputusan Manajerial pada Perusahaan Manufaktur - Muhammad Bachtiar Nur Fa’izi; Elsa Lestari; Jocelyn Lauren; Valleni Dwiana Putri; Vallena Eka Putri; Husni Mubarok (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
The purpose of this study is to examine how cost classification is used in management accounting and to what extent this information is used in the management decision-making process in manufacturing companies. Cost categories, such as fixed, variable, direct, and indirect, help managers understand the cost structure and assess operational efficiency. This study was conducted through a qualitative descriptive case study approach in one of the manufacturing companies in Indonesia. Direct observation, in-depth interviews, and internal company documentation were used to collect data. The results showed that, especially in budget planning, cost-volume-profit analysis, and selling price determination, proper cost classification plays a significant role in the decisionmaking process. However, some problems were found with the consistency of cost classification, which can affect the accuracy of management data.